Endoplasmic reticulum stress-induced cellular dysfunction and cell death in insulin-producing cells results in diabetes-like phenotypes in Drosophila. - Katsube, H.; Hinami, Y.; Yamazoe, T.; Inoue, Y.H. (Biology open, 2019)
The destruction of pancreatic ? cells leads to reduced insulin secretion and eventually causes diabetes. Various types of cellular stress are thought to be involved in destruction and/or malfunction of these cells. We show that endoplasmic reticulum (ER) stress accumulation in insulin-producing cells (IPCs) generated diabetes-like phenotypes in Drosophila To promote the accumulation of extra ER stress, we induced a dominant-negative form of a Drosophila ER chaperone protein (Hsc70-3DN) and demonstrate that it causes the unfolded-protein response (UPR) in various tissues. The numbers of IPCs decreased owing to apoptosis induction mediated by caspases. The apoptosis was driven by activation of Dronc, and subsequently by Drice and Dcp-1. Accordingly, the relative mRNA-expression levels of Drosophila insulin-like peptides significantly decreased. Consistent with these results, we demonstrate that glucose levels in larval haemolymph were significantly higher than those of controls. Accumulation of ER stress induced by continuous Hsc70-3DN expression in IPCs resulted in the production of undersized flies. Ectopic expression of Hsc70-3DN can induce more efficient ER stress responses and more severe phenotypes. We propose that ER stress is responsible for IPC loss and dysfunction, which results in diabetes-related pathogenesis in this Drosophila diabetes model. Moreover, inhibiting apoptosis partially prevents the ER stress-induced diabetes-like phenotypes.